PENGARUH DISTRIBUTIVE JUSTICE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DI MEDIASI OLEH TRUST IN ORGANIZATION DI PT INDOPORLEN - Warsindah, Lucy; Wulandari, Novi Ayu (Manajemen Bisnis Kompetensi, 2016)
ABSTRACTThis study aims to analyze the impact of distributive justice on organizational citizenship beÃ‚Âhavior mediated by trust in organization at PT Indoporlen, Bekasi. The purposive sampling method is used to spread the sampling questionnaire to 145 permanent employees in PT. Indoporlen. Data analysis method used by using descriptive statistical analysis with SPSS 22 and structural equation method (SEM) with AMOS 6.0. Based on the result of hypothesis testing, it can be concluded that distributive justice to organizational citizenship behavior has a ÃŽÂ² value of 0.451 with a significant value of 0.006 < 0.05, then H1 supported which means that distributive justice has positive influence on organizational citizenship behavior. While the results of distributive justice on organizational citizenship behavior mediated by trust in organization has a ÃŽÂ² value of 0.586 with a significant value 0f 0.000 < 0.05, then H2 is also supported which means there is an impact of distributive justice on organizational citizenship behavior mediated by trust in organization then with trust in organization as a mediator, it will increase the significant influence of distributive justice on organizational citizenship behavior. Implication managerial in this research that is can managers improve the delivery of wages in accordance with the performance of produced employees as well as the division of the working fair according to what has been agreed with company employÃ‚Âees , can managers increase attitude fair with give equality in treating employees , honest in providing information on to an employee , and true in treating employees , and manager also had to check and control employees at regular intervals in order to do the work which in accordance with the procedures which have been determined.Keywords: distributive justice, organizational citizenship behavior, and trust in organization